Literature Review: The Role of Kaizen in Improving the Quality of Automotive Products - Baharuddin, Siti Ruqaiyah; Anwar, Fahri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Global competition, digital transformation, and rising expectations for product quality all pose challenges for the automotive sector.  Kaizen, a concept of continuous improvement that is widely used in manufacturing processes, is one strategic way to address this challenge.  The purpose of this study is to examine the role of Kaizen in improving the quality of automotive products by conducting a comprehensive literature review of eleven selected scientific articles from national and international journals. The study found that Kaizen tools such as 5S, Poka-Yoke, PDCA, and Kaizen Costing were successful in reducing production errors and improving process efficiency.  However, cultural opposition, inadequate training, and adaptability to digital technologies all pose obstacles to Kaizen adoption.  This study shows that the effectiveness of Kaizen depends on management support, employee engagement, and the organization's capacity to incorporate technology into the philosophy of continuous improvement.  This research provides a foundation for building a Kaizen strategy in the Industry 4.0 era.